Impact of a training program on hospital pharmacists' patient-centered communication attitudes and behaviors - Yew Keong Ng; Noraida Mohamed Shah; Timothy F. Chen; Navin Kumar Loganadan; Shue Hong Kong; Yi Yun Cheng; Siti Shahida Md Sharifudin; Wei Wen Chong (Elsevier, 2023)
Background: Effective communication that integrates the value of patient-centered care is important in healthcare encounters. Communication skills training (CST) has been indicated as effective in improving patient-centered communication behaviors. However, there is a paucity of studies on the impact of CST among Malaysian hospital pharmacists. Objective: This study aimed to evaluate the effects of a patient-centered CST program on patient-centered communication scores, communication self-efficacy, and attitudes toward concordance among pharmacists in public hospitals. Methods: A communication skills training (CST) program was conducted among hospital pharmacists. This training intervention was developed based on patient-centered communication frameworks and techniques, namely the Four Habits Model and motivational interviewing. A pre-test/post-test quasi-experimental design was implemented for the evaluation. Pharmacists underwent pre-test/post-test audiotaped simulated consultations and completed questionnaires, including the Revised United States-Leeds Attitudes Toward Concordance scale (RUS-LATCon) and Communication Self-Efficacy scale. The Four Habits Coding Scheme (FHCS) was used to evaluate patient-centered communication scores from the audiotapes, and the Wilcoxon signed-rank test was used to analyze for differences in the pre- and post-intervention scores. Results: A total of 38 pharmacists from four tertiary hospitals participated in this study and completed the pre-test. However, due to the impact of COVID-19, only 23 pharmacists completed the post-test data collection. Improvements were noted in the FHCS scores post-training, including items related to exploring patients' concerns, acceptability, and barriers to treatment. Based on the questionnaire, there was an improvement in recognizing patients' needs and potential medication uncertainty and an increase in the overall communication self-efficacy scores after the training. Conclusions: CST may help improve the adoption of patient-centered communication in pharmacists' consultations with patients.